Was Smith a moral subjectivist? - Kevin Quinn (Economic Thought, 2019)
This paper challenges the commonly held view that Smith's moral theory is a subjectivist theory. Smith's test for goodness and rightness - for propriety - is not the approbation of an impartial spectator, but the warranted approbation of such a spectator. Something is right or good not because an impartial spectator would approve of it, but because such a spectator would be warranted in so approving.
Keywords: B12; B31; 330; Adam Smith; impartial spectator